IMPLEMENTATION OF REGIONAL REGULATION POLICIES IN HANDLING FLOOD DISASTERS IN SOUTH TANGERANG CITY (Case Study: Communication, Human Resources, Disposition and Bureaucratic Structure) - Muhamad Taslim; Evi Satispi; Fal Harmonis (EKOSSISTEM : Islamic Economics, Banking, Law, System, 2025)
The research method used is a qualitative approach with a case study design. Data was collected through in-depth interviews with local government officials, analysis of policy documents, and field observations in flood- prone locations. This approach allows researchers to gain a deeper understanding of the dynamics that occur in the handling of flood disasters.